Global Sea Ice Drift Climate Data Record Release v1.0 - Multimission ... : OSI-455 ... - OSI SAF; EUMETSAT SAF On Ocean And Sea Ice (EUMETSAT SAF on Ocean and Sea Ice, 2022)
Daily sea ice drift vectors, processed from passive microwave satellite data (SSM/I, SSMIS, AMSR-E and AMSR2) over the polar regions. Continuous maximum cross-correlation is used to calculate ice drift, including use of a wind-driven free-drift model in the summer melt season. This is a Thematic Climate Data Record (TCDR). Besides the Thredds server, mentioned in the resources, another way to access this product is through the FTP server ftp://osisaf.met.no/reprocessed/ice/drift_lr/v1 ...